Thai Usage among Chinese Students : A Case Study of Chinese Students’ Thai Writing Problems, Master of Arts program in Communicative Thai as a Second Language, Huachiew Chalermprakiet University - โมสิกรัตน์ ธิดา; ธรรมวาจา วิไล; อธิเลิศธนานนท์ พิฐชญาณ์; สัมภวะผล วนิสา (Academic and Research Journal of Liberal Arts (Online), 2018)
The purpose of this research is to 1) study the Thai writing problem of Chinese Students taking Communicative Thai as a second language program at Huachiew Chalermprakiet University and 2) discuss the problem with the instructors and Chinese students to figure out the way to improve their Thai writing skill. This qualitative research started from analyzing students’ worksheets and activities in two courses, TC 8253 Advance Thai Writing and TC 8263 Advance Thai Reading, of 2013 – 2014 academic years. Research populations were Chinese students who enrolled the two courses in the stated academic years. The two sample groups in this research consist of a group of thirty three students specially selected and a conversational group of twenty students randomly chosen along with six Thai instructors who teach foreign students. The research found that Chinese students have difficulty writing Thai in the following aspects 1) Word level – wrong word choice, misspelling, absence of spaces, and wrong punctuations 2) Sentence level – grammatical errors, mixing spoken language with written language, and incomplete sentences 3) Paragraph level – lack of unity, coherence and theme, and incompletion of elements. From the discussion with the randomly selected students and Thai instructors, it is agreed that problems of Thai writing are caused by the lack of Thai grammatical knowledge and insufficient practice of language skill. The recommended solution is to provide a course of learning all four language skills and include grammar lessons in other subjects. In addition, Thai reading and writing activities should be promoted also.